Layer-by-layer growth of ε-Ga2O3 thin film by metal–organic chemical vapor deposition. (29th August 2018) - Chen, Zimin; Li, Zeqi; Zhuo, Yi; Chen, Weiqu; Ma, Xuejin; Pei, Yanli; Wang, Gang
Abstract: Layer-by-layer morphology is a crucial signature of the quality of epitaxial thin films. In this study, layer-by-layer growth of an ε-phase gallium oxide (ε-Ga2 O3 ) thin film is demonstrated using metal–organic chemical vapor deposition. A two-step growth method, in which a nucleation layer is grown at 600 °C and an epilayer is grown at 640 °C, is employed to fabricate a high-quality ε-Ga2 O3 thin film on a c -plane sapphire substrate. The morphology of the ε-Ga2 O3 film is evaluated by atomic force microscope. The density of screw-type threading dislocations determined by an X-ray diffraction rocking curve is as low as 1.8 × 10 8 cm −2 .